Pengaruh Keselamatan Kesehatan Kerja (K3), Kompetensi dan Disiplin Terhadap Kinerja Karyawan PT. Patri Agung Perdana - Musa, Chalid Imran (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to examine the influence of Occupational Health and Safety (OHS), Competence, and Discipline on employee performance at PT. Patri Agung Perdana in Banyuasin. The population consisted of 105 employees, with a sample of 84 respondents selected using probability sampling and the cluster sampling method. Primary and secondary data were used, collected through questionnaires. The data were analyzed using multiple linear regression analysis. The results show that OHS, Competence, and Discipline simultaneously have a positive and significant effect on employee performance. Individually, OHS, Competence, and Discipline each have a positive and significant effect on employee performance. The coefficient of determination indicates that OHS, Competence, and Discipline contribute 72% to employee performance, while the remaining 28% is influenced by other factors not examined in this study.